Hubungan antara Dukungan Suami dan Tingkat Kecemasan dalam Menghadapi Persalinan pada Ibu Hamil Primigravida Trimester Ketiga - Akmal Maulana; Lia Herlina; Tetet Kartilah; Tetik Nurhayati (Jurnal Persada Husada Indonesia, 2026)
Research Objective: Anxiety commonly occurs among primigravida women as childbirth approaches. This study aimed to examine the association between husband support and anxiety levels among third-trimester primigravida women in the working area of Purbaratu Public Health Center. Methodology: This quantitative study used a cross-sectional design and total sampling of 30 eligible participants. Husband support was measured using a modified Guttman-scale questionnaire, while anxiety was assessed using the Hamilton Anxiety Rating Scale (HARS). Descriptive analysis and the Fisher-Freeman-Halton exact test for a 2 × 3 contingency table were used, with Cramér’s V reported as an effect-size measure. Results: Most respondents received husband support and experienced mild anxiety. Husband support was significantly associated with anxiety level (p = 0.001), with a Cramér’s V of 0.66, indicating a strong association in this sample. Conclusion: Husband support was associated with lower anxiety levels among third-trimester primigravida women. Because the study was cross-sectional, the findings do not establish causality. Involving husbands in antenatal education may support maternal psychological preparedness for childbirth.